INTERNATIONALIZATION OF THE TEXTILE AND TAILORING COMPANIES OF AREQUIPA AND THE IMPACT ON THEIR DEVELOPMENT - Heningns Otoya, Julio Alberto (2012)
The investigation seeks to determine whether the internationalization processes followed in recent years by the textile and tailoring companies in the region of Arequipa in Peru, have impacted positively on their development, enabling improvements in competitive and economic sustainability. The results of the sample, permit to affirm a beneficial effect over the development of such organizations when they focus part of their performance in international markets, allowing that the adaptation to more demanding standards promotes incremental sales volumes, generate competitive advantages in different areas and improve the organization favoring their “new knowledge”. When these factors are empowered in a virtuous circle, the companies are gaining an increasing competitive level and reinforce its sustainability over the time. The research is descriptive, longitudinal, explanatory and documentary, and in this were revised statistics, reports of the selected companies, and media reports related to the topic. Also, in order to enhance knowledge and gain further evidence was observed in situ companies and their executives and major customers were surveyed.